Emerging organic compounds in European groundwater. (15th January 2021) - Bunting, S.Y.; Lapworth, D.J.; Crane, E.J.; Grima-Olmedo, J.; Koroša, A.; Kuczyńska, A.; Mali, N.; Rosenqvist, L.; van Vliet, M.E.; Togola, A.; Lopez, B.
Abstract: In Europe, emerging organic compounds (EOCs) in groundwater is a growing research area. Prioritisation for monitoring EOCs in Europe was formalised in 2019 through the development of the first voluntary groundwater watch list (GWWL). Despite this, groundwater occurrence data in the peer reviewed literature for Europe has not been reviewed to date. Questions surrounding the effect, toxicity, movement in the subsurface and unsaturated zone make the process of regulating EOC use difficult. The aim in Europe is to develop a unified strategy for the classification, and prioritisation of EOCs to be monitored in groundwater. This paper compiles evidence from the recent published studies from across Europe, since 2012, when the last major literature global review of EOCs in groundwater took place. A total of 39 studies were identified for review based on specific selection criteria (geography, publication date, sample size>10, inclusion of EOCs data). Data on specific compounds, and associated meta-data, are compiled and reviewed. The two most frequently detected EOCs, carbamazepine and caffeine, occurred in groundwater at concentrations of up to 2.3 and 14.8 μg/L, respectively. The most frequently reported category of compounds were 'Pharmaceuticals'; a highly studied group with 135 compounds identified within 31 of the 39 studies. In Europe, the majority of reviewed studies (23) were at a regional scale, looking specifically at EOCs in a specific city or aquifer. The use of analytical methods is not uniform across Europe, and this inevitably influences the current assessment of EOCs in groundwater. A correlation between the number of compounds analysed for, and the number detected in groundwater highlights the need for further studies, especially larger-scale studies throughout Europe. For the development of EU and national regulation, further work is required to understand the occurrence and impacts of EOCs in groundwater throughout Europe and elsewhere. Graphical abstract: Image 1 Highlights: 39 studies reviewed to assess occurrence of EOCs in European groundwater. Most reported category 'Pharmaceuticals'. Maximum carbamazepine and caffeine concentrations 2.3 μg/L, and 14.8 μg/L respectively. Strong correlation between number of compounds screened for and detections. Standardised reporting needed to assess the current compounds of emerging concern. Abstract : Assessing the occurrence of emerging organic compounds in European groundwater; implications for environmental exposure.